Evaluación de la contaminación física, química y bacteriológica del agua del río Nanay en los tramos: bocatoma agua potable/zanjón refinería Iquitos-Loreto-2018 - Cortez Galindo, Cesario (2022)
The objective of this research is to evaluate the physical, chemical and bacteriological contamination of the water of the Nanay river – drinking water intake intake – Pampachica and Petroperú Refinery trench, located in the province of Loreto, Peru; during the months of August and December of the year 2018. The physical analysis used the HASH-Electrometric technique to measure electrical conductivity, pH and air temperature. In the chemical analysis, the techniques of titration, colorimetry, and spectrometry were used, and in the bacteriological analysis, the technique of multiple NMP fermentation tubes was used. Four stationary reference points 500 m above and 500 m below were taken for in situ and laboratory analyses. The results of the problem samples of the physical parameters were found: pH with a variation of 6.03 in the intake 500 m below the pH unit to 6.07 pH unit in the intake 500 m above the drinking water catchment and chemical parameters: Dissolved oxygen from 0.97 mg/L to 1.75 mg/L of the water in the Petroperú intake and refinery, which presents a high risk level for the aquatic environment, normalized by Supreme Decree No. 004-2017 -MINAM, which approves Environmental Quality Standards (ECA); for water, the average iron ranges between 0.83 mg/L – 8.16 mg/L which does not present what is admissible in the standards of the World Health Organization and the European Union.